Основные правовые проблемы прав человека в области современной медицины и пути их решения в условиях развития современного общества - Береговцова, Д.; Beregovtsova, D. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статье исследуются основные правовые проблемы, возникающие в ходе применения к человеку новейших медицинских технологий. Автор приходит к выводу, что достижения современной медицины способны не только принести несомненную пользу человечеству в целом и конкретному индивиду в частности, но и нанести значительный ущерб правам и свободам человека и поэтому нуждаются в детальной правовой регламентации с целью минимизации возможных злоупотреблений в процессе их применения. The article examines the main legal issues arising in the application of new medical technologies to man. The author notes that the advances in modern medicine can not only bring benefit to mankind in general, and specific individual in particular, but also cause significant harm to the rights and freedoms of man and therefore they need detailed legal regulation with the aim of minimizing the possible abuses in the process of their application. The author comes to the conclusion about the existence of human rights groups, the most exposed to as a positive the negative influence of modern medicine, but alsonotes that the rapid development of medicine leadsto the isolation of new rights and freedoms, as well as expanding the content of existing ones. The article also notes that, despite the obvious danger associated with the use of modern medical technology, there has recently been a trend towards permissive legal regulation of the discussed public relations, and increasingly the most controversial technology is recognized by the legislators of foreign countries to be permissible and acceptable. However, the main task of law should bethe protection of human rights in the context of rapid development of modern medicine, which should be achieved both on the individual level and at the levelof society and eventually of humanity as a whole.
Main Legal Problems of Human Rightsin the Field of Modern Medicine and Ways of their Solution in Conditions of Modern Society Development.
Keywords: научно-технический прогресс в области биологии и медицины; права человека в области современной медицины; право на уважение достоинства; право на жизнь; право на здоровье; право на психофизическую неприкосновенность; scientific and technological progress in biology and medicine; human rights in the field of modern medicine; the legal problems of human rights in the field of medicine; right to dignity; right to life; right to health; right to psychophysical integrity